Islamist and secular forces in Morocco: Not a zero-sum game - Mohammed Masbah (Stiftung Wissenschaft und Politik (SWP), 2014)
In Morocco, unlike in other Arab countries, Islamists and seculars tend to cooperate in formal as well as informal politics. Political opportunities and pragmatic interests trump ideology most of the time, providing a suitable environment for a broadly inclusive political order. However, two factors stand in the way of sustained cooperation between Islamist and secular currents: on the one hand, sporadic upsurges of identity politics, and on the other, the strategies of divide and rule traditionally pursued by the "Makhzen" and its close allies. Rather than focusing on a set of partners who appear at first to be compatible with their values, Europeans should promote an inclusive political process that integrates all actors with significant popular outreach, such as the social movement Jama'at Al-Adl wa-l-Ihsan (Justice and Charity Association, AWI). (SWP Comments)
Keywords: 320